Corporation tax - Carmichael, K. S. (London : H. F. L. (Publishers), 1978)
This edition incorporates all the legislation relating to corporation tax up to and including the Finance Act 1978 which is was current at the time.
Includes index
Loans
Keywords: Corporations--Taxation